The protection of cultural heritage during armed conflict : the changing paradigms - Higgins, Noelle (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The book queries whether using the genocide framework is an appropriate response to attacks on cultural heritage. This volume will be an essential resource for scholars and practitioners in the areas of international law, international humanitarian law, international criminal law, the rights of minorities and cultural heritage law"--
Introduction -- Traditional paradigms on the protection of cultural heritage during armed conflict -- Potential paradigms: cultural cleansing, the responsibility to protect doctrine and cultural genocide -- The securitisation of cultural heritage -- Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Cultural property -- Protection (International law); International criminal law; LAW / General; LAW / Civil Rights; LAW / Criminal Law / General